Purine Metabolism and Rett Syndrome - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1996)
Levels of purine and pyridine nucleotides and their metabolites were determined in erythrocytes and plasma of 31 Rett pattients and 17 age-matched controls at the Departments of Molecular Biology and Child Psychiatry, University of Siena, Children's Hospital, Siena, Italy.